Sustainable microwave-assisted solketal synthesis over sulfonic silica-based catalysts. Issue 6 (December 2022) - Aguado-Deblas, Laura; Estevez, Rafael; Russo, Marco; La Parola, Valeria; Bautista, Felipa M.; Testa, Maria Luisa
Abstract: Sulfonic and propylsulfonic silica-based catalysts were synthesized, characterized and tested in the acetalization of glycerol (G) by a sustainable, solvent-free and fast procedure, under microwave irradiation, to produce solketal (S). The catalysts were prepared by different grafting procedures and their surface and structural properties were investigated by means of N2 adsorption isotherms, Thermogravimetric Analysis (TGA), X-ray Photoelectron Spectroscopy (XPS) and X-Ray Fluorescence Spectroscopy (XRF). Under the optimized reaction conditions (Temperature 40 °C, microwave power ˂100 W, time 2 min and 1:12 glycerol/acetone molar ratio) the sulfonic materials, produced by the hydrothermal grafting, showed excellent performance in terms of activity, selectivity and stability, with no leaching of sulfonic groups after several cycles. By the correlation of the structure properties of the materials and their activity, the performance of the catalysts was shown strictly correlated both to the acidity and the surface density of the active sites. Graphical Abstract: ga1 Highlights: Sulfonic silica catalysts showed excellent performance and stability in MW-assisted solketal synthesis. Hydrothermal (HT) grafting allowed to insert the highest amount of active sites. MW improve the performance of the catalysts under an optimized green and fast procedure (T 40 °C, MP ˂100 W, t 2 min). The performance of the catalysts is strictly correlated to the acidity and the acid surface density.